2012
DOI: 10.1016/j.micpath.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative meta-analysis of the effect of Lactobacillus species on weight gain in humans and animals

Abstract: Different Lactobacillus species are associated different effects on weight change that are host-specific. Further studies are needed to clarify the role of Lactobacillus species in the human energy harvest and weight regulation. Attention should be drawn to the potential effects of commonly marketed lactobacillus-containing probiotics on weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
241
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(262 citation statements)
references
References 36 publications
12
241
3
6
Order By: Relevance
“…Our findings are consistent with prior observations that rodents fed VSL#3 (12) and other single strain probiotic supplements (24)(25)(26)(27) gained less body mass and fat mass during high-fat feeding compared to controls (12). Our findings are also consistent with recent observations (9) that young, healthy subjects consuming a single probiotic strain (Lactobacillis casei Shirota) gained less body and fat mass during a high-fat diet compared with placebo.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with prior observations that rodents fed VSL#3 (12) and other single strain probiotic supplements (24)(25)(26)(27) gained less body mass and fat mass during high-fat feeding compared to controls (12). Our findings are also consistent with recent observations (9) that young, healthy subjects consuming a single probiotic strain (Lactobacillis casei Shirota) gained less body and fat mass during a high-fat diet compared with placebo.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggested that some species of Lactobacillus are associated with weight gain in human and animal infants [37][38][39] . Nevertheless, the body weight of the BFE group was not significantly higher than that of the PFE group, which was not consistent with the statement by Million 40 that Lactobacillus would lead to obesity or weight gain. The results we obtained were in agreement with Lahtinen 41 , who suggested that some species of Lactobacillus would be associated with weight gain in infancy but not in human and animal adults.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies in humans and animals reported conflicting results on the effects of different Lactobacillus strains on body weight (9). In humans, ingestion of prebiotics has been shown to influence gut microbiota composition (10), perhaps alter intestinal permeability, and increase plasma GLP-1 concentrations and decrease postprandial glucose concentrations (11).…”
mentioning
confidence: 99%